Representativeness of European biochar research: part II – pot and laboratory studies - Sakrabani, Ruben; Kern, Jurgen; Mankasingh, Utra; Zavalloni, Costanza; Zanchettin, Giulia; Bastos, Ana Catarina; Tammeorg, Priit; Jeffery, Simon; Glaser, Bruno; Verheijen, Frank G. A. (Taylor & Francis, 2017)
Biochar research is extensive and there are many pot and laboratory studies carried out in Europe to investigate the mechanistic understanding that govern its impact on soil processes. A survey was conducted in order to find out how representative these studies under controlled experimental conditions are of actual environmental conditions in Europe and biomass availability and conversion technologies. The survey consisted of various key questions related to types of soil and biochar used, experimental conditions and effects of biochar additions on soil chemical, biological and physical properties. This representativeness study showed that soil texture and soil organic carbon contents used by researchers are well reflected in the current biochar research in Europe (through comparison with published literature), but less so for soil pH and soil type. This study provides scope for future work to complement existing research findings, avoiding unnecessary repetitions and highlighting existing research gaps.
Keywords: biochar; soil; Europe; pot experiments; laboratory scale; representativeness